2008
DOI: 10.1007/s11562-007-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

Women, piety and practice: A study of women and religious practice in Malaysia

Abstract: While the definition of religion in sociology has been highly contentious, we define religion in this article as simply the acts of piety that are conducted within the religious sphere. The point of this definition is to draw attention to practice and away from belief. This approach to religion appears to be especially useful in the case of contemporary Islam, where female piety has become a significant aspect of religious renewal. The idea of a religious sphere is taken from the work of Luc Boltanski and his … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Keadaan ini mewujudkan suatu paradoks kerana teks budaya bukan Barat seperti Korea Selatan yang digunakan pihak kerajaan untuk mengimbangi aliran teks budaya Amerika menerusi Dasar Pandang ke Timur dan nilai-nilai Asia mewujudkan perdebatan kritikal mengenai isu-isu yang berkaitan dengan budaya, identiti nasional dan Islam yang membentuk idea kemodenan Malaysia. Namun, isu yang lebih penting adalah kontroversi mengenai wanita Melayu dan K-pop telah mewujudkan satu lagi persoalan mengenai wanita dalam konteks projek kemodenan di negara ini (Tong & Turner, 2008). Justeru, artikel ini berhujah bahawa wanita Melayu mempunyai pendekatan ketidakpatuhan strategik yang digunakan dalam proses penggunaan budaya popular Korea dan perkaitannya dengan pembinaan imaginasi kemodenan popular.…”
Section: Pengenalanunclassified
“…Keadaan ini mewujudkan suatu paradoks kerana teks budaya bukan Barat seperti Korea Selatan yang digunakan pihak kerajaan untuk mengimbangi aliran teks budaya Amerika menerusi Dasar Pandang ke Timur dan nilai-nilai Asia mewujudkan perdebatan kritikal mengenai isu-isu yang berkaitan dengan budaya, identiti nasional dan Islam yang membentuk idea kemodenan Malaysia. Namun, isu yang lebih penting adalah kontroversi mengenai wanita Melayu dan K-pop telah mewujudkan satu lagi persoalan mengenai wanita dalam konteks projek kemodenan di negara ini (Tong & Turner, 2008). Justeru, artikel ini berhujah bahawa wanita Melayu mempunyai pendekatan ketidakpatuhan strategik yang digunakan dalam proses penggunaan budaya popular Korea dan perkaitannya dengan pembinaan imaginasi kemodenan popular.…”
Section: Pengenalanunclassified
“…Amin (2004) argues that women's employment (as well as fertility) in Malaysia also depend (apart from women's tastes and preferences) on social values and culture. Although it will be touched upon here only briefly, the changing role of women and the view of the family at the intersection of "Islamization projects" and state and economic interests in Malaysia have been the topic of lively discussions (Kooi-Chin Tong & Turner, 2008;Ong, 1990). Stivens (2006), for example, argues that the highly politicized discourse from the state, religious leaders, and the media around family values in Islam has had a significant impact on Malay women.…”
Section: "I Am Too Old!": Reasons Not To Reenter the Labor Marketmentioning
confidence: 99%
“…As we shall see, two recent studies have highlighted the centrality of halal certified food to the local Malay Muslim community’s religious identity and their expression of personal piety (Nasir & Pereira 2008; Nasir et al. 2010; see also Tong & Turner 2008). Nasir and Pereira, for instance, have suggested that Malay Muslims in Singapore adopt what they define as ‘defensive dining’ to maintain their halal practices within nonhalal contexts.…”
Section: Introductionmentioning
confidence: 99%